Nursing Home and Elderly Care Center in Purwokerto City with Healing Architecture as Design Approach - Angie Arliani; Eko Budi Santoso; Didik Nopianto Agung Nugradi (Canopy: Journal of Architecture, 2025)
The increasing elderly population in Purwokerto highlights the need for residential and care facilities that address their physical, psychological, and social needs. This design of an Elderly Home and Care Center adopts a Healing Architecture approach to create an environment that supports recovery and enhances quality of life. An analysis of elderly needs, including behavior patterns, health challenges, and social aspects, serves as the basis for determining the design concept, spatial layout, and architectural elements. The result is an integrated, adaptive, and humane facility that functions not only as a residence but also as a comprehensive elderly care center.